Market Microstructure in Emerging and Developed Markets - H. Kent Baker; Halil Kiymaz (The @Robert W. Kolb series in finance, 2013)
A comprehensive guide to the dynamic area of finance known as market microstructureInterest in market microstructure has grown dramatically in recent years due largely in part to the rapid transformation of the financial market environment by technology, regulation, and globalization. Looking at market transactions at the most granular level—and taking into account market structure, price discovery, information flows, transaction costs, and the trading process—market microstructure also forms the basis of high-frequency trading strategies that can help professional investors generate profits and/or execute optimal transactions.Part of the Robert W. Kolb Series in Finance, Market Microstructure skillfully puts this discipline in perspective and examines how the working processes of markets impact transaction costs, prices, quotes, volume, and trading behavior. Along the way, it offers valuable insights on how specific features of the trading process like the existence of intermediaries or the environment in which trading takes place affect the price formation process.Explore issues including market structure and design, transaction costs, information flows, and disclosureAddresses market microstructure in emerging marketsCovers the legal and regulatory issues impacting this area of financeContains contributions from both experienced financial professionals and respected academics in this fieldIf you're looking to gain a firm understanding of market microstructure, this book is the best place to start.